Institutional Pediatric Convulsive Status Epilepticus Protocol Decreases Time to First and Second Line Anti-Seizure Medication Administration. (October 2020) - Trau, Steven P.; Sterrett, Emily C.; Feinstein, Lydia; Tran, Linh; Gallentine, William B.; Tchapyjnikov, Dmitry
Highlights: Pediatric Status Epilepticus is a medical emergency in which there are frequent delays to anti-seizure medication administration. A paper-based pediatric convulsive status epilepticus treatment protocol may decrease the time to anti-seizure medication administration. Improvement in anti-seizure medication administration times after status epilepticus treatment protocol implementation are most evident in the improved timeliness of second line non-benzodiazepine agent administration. Benzodiazepines continue to be frequently under-dosed even after protocol implementation. Abstract: Purpose: Convulsive status epilepticus (CSE) is a medical emergency associated with high rates of morbidity and mortality. Although guidelines for CSE management recommend rapid treatment of seizures, prior studies show that compliance with these guidelines is low. In this study, we assessed if implementation of a paper-based clinical pathway for the treatment of CSE improves the timeliness and appropriate dosing of first and second line anti-seizure medications (ASM). Methods: A non-digital CSE treatment protocol was implemented as part of a quality improvement initiative in 2016. A retrospective analysis was subsequently conducted on cases of CSE originating in the pediatric emergency department (ED) from 2012-2019. Standard descriptive statistics were used to assess patient demographics as well as the timing and dosing of the first and second line ASMs used in our protocol (lorazepam [LZP] and fosphenytoin [FOS]). Statistical process control charts (X m R charts) were used to assess the variation in time to drug administration before and after implementation of the protocol. Results: 153 cases of CSE were identified (72 prior to and 81 after protocol implementation). Among patients who were actively having seizures on arrival to the ED (n = 44), the median time from arrival to ASM administration decreased from 15 to 11 minutes for the first LZP dose (p = 0.23), 23 to 10 minutes for the second LZP dose (p = 0.06), and 40 to 25 minutes for the PHE dose (p = 0.04). There was no improvement in time to LZP administration after seizure onset among those with seizure onset after hospital arrival (5 minutes before/after implementation for the first LZP dose and 15 to 14 minutes for second LZP dose); however, the time to FOS decreased from 42 to 22 minutes (p = 0.86). Statistical process control charts showed a universal decrease in variation for time to each drug administration after protocol implementation. Whereas FOS dosing was largely appropriate before and after protocol implementation, appropriate dosing of LZP did not improve, with only about half of patients receiving the recommended dose. Conclusion: The implementation of a paper-based treatment protocol for CSE was associated with a decreased time to ASM administration among patients who arrived to the ED, particularly for the second-line ASM. Approaches for improving appropriate benzodiazepine dosing are needed.